Test of relativity: Determination of Mercury's apsidal motion excess using transit photographic data. Issue 9 (November 2013) - Constantin, D.R.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract In this paper we determine the excess in Mercury's apsidal motion rate using, as a new approach, photographic observations of the planet transits on the solar disk during the period 1927–1973. Prior to compute the equations of condition in equatorial coordinates, we obtain the 616 small differences O –C (observed – calculated) in (α, δ), which are in the interval [–6″, 6″]. Using these results, via the Simon‐Bretagnon ephemeris and the least squares method (LSQ Method), we compute the variations corrections for the orbital elements λ, e, ϖ. As regards the relativistic theory, we obtain the perihelion longitude variation correction δϖ ′ = –1′′.7 cy–1 which is negative, this fact being consistent with a slightly diminished value for Mercury's relativistic excess. Since this correction is of arcseconds order, we conclude that Mercury's transits photographic observations in coordinates confirm the excess in Mercury's apsidal motion rate deduced in General Relativity. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)